Relationship of extender and packaging system an the length of preservation and the quality of chilled semen of Boer goat - Arie Febretrisiana; . Anwar; Simon Sinulingga (Jurnal Ilmu Ternak dan Veteriner, 2016)
The aim of this research was to compare the effectiveness of different extender (either Triladyl or Tris Egg Yolk extender) and different packaging method (pool and straw) of chilled semen an the length of preservation and the quality of chilled semen of Boer goat. Semen was collected using an artificial vagina from 3 two years old Boer bucks with body weight of 50-55 kg. It was evaluated under a microscope, then each was diluted either in Tris egg yolk extender (TEY) or Triladyl. Those diluted sperms were then packed either in pool or straw and preserved at 5⁰C refrigerator. Sperm motility, viability and membrane integrity of each group were evaluated every 24 h for up to 5 days. Results showed that sperm motility in Triladyl of  pool packaging system up to 3 days was higher than straw packaging system or TEY in pool or straw packaging system which were 45.8%, 26.1%, 32.1% and 9.1%, respectively (P<0.05). Percentage of sperm membrane integrity showed the same pattern to Triladyl both in pool and straw packaging system which was higher than TEY group (75.2% and 77,2%; P<0.05). Sperm viability in Triladyl both in pool or straw packaging system decreased (P<0.05) after 3 days of preservation (77.1% and 76.2%) but TEY significanly decreased after 4 days of preservation either in pool or straw packaging system (73.2% and 58.0%; P<0.05). It was concluded that sperm quality decreased with increasing of the length of preservation while Triladyl extender in pool packaging system showed the best quality.Key Words: Chilled Semen, Boer, Triladyl, Tris Egg Yolk, Straw